Žemutinio pakilimo balsiai Pašušvio šnektoje - Kazlauskaitė, Rūta (Kalbotyra, 2001)
The article is devoted to the low vowels of the Pašušvys subdialect which belongs to the northern West-Aukštaitian dialect. The subdialect under analysis has the following sets of low vowels: in unstressed syllables the short [a a. ȧ], [e æ ẹ]; in stressed syllables the short [a ȧ], [æ e], the half-long [a. ȧ.], [æ. e.], and the long [a. ȧ.], [æ. e.]. The long vowels [e.], [ẹ.], [ie] are shortened to the short [e ẹ] in unstressed syllables. The reasons conditioning the appearance of new, the a type, vowels are the nonpalatalization or certain consonants, vowel assimilation, analogical vowel change. contraction, or the influence of semantically or phonetically related words. In word-medial and word-final positions the back vowels are followed by non-palatalized consonants and the front are followed by palatalized consonants. In word-initial position the back vowels are used due to the neutralization of the opposition of the low [e e. e.] vs [a a. a.].In this way, there are three low phonemes in the Pašušvys subdialect: short /a/, half-long /a./, and long /a./.